2007
DOI: 10.1200/jco.2006.08.9540
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity in a Randomized Phase III Trial of Intra-Arterial Compared With Intravenous Cisplatin Chemoradiation in Patients With Locally Advanced Head and Neck Cancer

Abstract: Depending on the criteria used to assess hearing loss due to treatment, differences in ototoxicity between CRT-IA and CRT-IV were found in favor of CRT-IA. It is desirable to specify hearing loss criteria toward frequencies vital for speech perception, and to refine grading scales to reveal subtle and clinically relevant dissimilarities in ototoxicity between different treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 41 publications
1
87
2
3
Order By: Relevance
“…In the present study, the median dose per infusion of cisplatin was 111 mg, less than 80 mg/m 2 . In contrast, in the cases of Madasu et al and Zuur et al, who followed the RADPLAT protocol, the dose per infusion of cisplatin was 150 mg/m 2 [10,11]. The median dose per infusion of cisplatin was 267 mg/m 2 in the report by Zuur et al [11].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In the present study, the median dose per infusion of cisplatin was 111 mg, less than 80 mg/m 2 . In contrast, in the cases of Madasu et al and Zuur et al, who followed the RADPLAT protocol, the dose per infusion of cisplatin was 150 mg/m 2 [10,11]. The median dose per infusion of cisplatin was 267 mg/m 2 in the report by Zuur et al [11].…”
Section: Discussioncontrasting
confidence: 46%
“…On the other hand, in our data, the mean thresholds of the AC after CRT-IA at frequencies below 8 kHz were almost the same as those before CRT-IA. Zuur et al also reported hearing loss caused by intra-arterial cisplatin chemoradiation, particularly at ultra-high frequencies [11]. In their study, the mean total threshold shift at PTA AC 8, 10, and 12.5 kHz was 20.4 dB for CRT-IA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…19,20 In our experience, despite lengthy surgical procedures, children are typically extubated within 12 hours of surgery.…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…A simultaneous intravenous infusion of sodium thiosulfate was given to inactivate any cisplatin that might enter the systemic circulation and to prevent side effects of systemic cisplatin such as renal failure, hearing loss, hair loss, nausea, and vomiting. 19 Constant physical A 6-year-old boy had a history of chronic constipation, acute abdominal pain, and abdominal distension. Computed tomography revealed peritoneal carcinomatosis and massive ascites with no renal or hepatic involvement.…”
Section: Nursing Implicationsmentioning
confidence: 99%